2020
DOI: 10.17239/l1esll-2020.20.01.01
|View full text |Cite
|
Sign up to set email alerts
|

The impact of syntactic and lexical trainings on capitalization of nouns in German in grade five

Abstract: Many orthographies include syntactic markers not represented in phonology. In general, to correctly use these syntactic markers, learners have to analyze and understand the syntactic context of the word to be written. Capitalization of nouns, a syntactic marker in German, involves marking heads of noun phrases and is challenging for learners. The aim of this intervention study was to evaluate the effects of syntactic and lexical based trainings on capitalization of nouns. 114 Luxembourgish fifth-graders were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Similar to learners with learning disabilities, poor capitalizers might need more extensive explicit instruction in order to detect the inflected NP unit and, thus, the capitalized noun. Intervention studies have already shown that a scaffolded syntactic approach shows positive effects (Bîlici et al, 2019;Brucher et al, 2020;Wahl et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to learners with learning disabilities, poor capitalizers might need more extensive explicit instruction in order to detect the inflected NP unit and, thus, the capitalized noun. Intervention studies have already shown that a scaffolded syntactic approach shows positive effects (Bîlici et al, 2019;Brucher et al, 2020;Wahl et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nominalizations are words belonging to a different lexical category (e.g., verbs or adjectives) that function as the nucleus of a NP and are thus transformed into a syntactic noun (Korth, 2013). Several empirical studies have shown that capitalization was best for concrete nouns and worst for nominalizations, as well as best for the NP structure DN and worst for N (Betzel, 2015;Bîlici et al, 2019;Brucher et al, 2020;Rautenberg & Wahl, 2019). These studies included children from second grade in primary school to secondary school.…”
Section: Introductionmentioning
confidence: 99%
“…des Graphems (<im Eifer>, <beim Niesen>). Das Erlernen der Großschreibung beginnt in der Grundschule, dabei hat sich die Analyse der Nominalphrase als effektiver didaktischer Ansatz erwiesen (Brucher, Ugen & Weth, 2020;Röber-Siekmeyer, 1999). Zusätzlich zu der Erweiterungsprobe (d. h. ob das Nomen durch Linksattribute beschrieben werden kann: <das vereinbarte Treffen>, <gute Gründe>) soll die Aufmerksamkeit auf die Deklinationen gelenkt werden (vgl.…”
Section: Meilenstein 8 -Großschreibung Je Nach Phrase Oder Satzunclassified
“…Training effects are reported for English past-tense spelling (Nunes et al, 1997a) and the apostrophe (Bryant et al, 1997), for French plural markers (Thévenin et al, 1999;Bîlici et al, 2018) and for German (Bîlici et al, 2020). A training that focused on noun phrases in a sentence found effects on capital spelling of nouns, even if controlled with a group that focused on the lexical category noun (Brucher et al, 2020).…”
Section: Training Of Syntactic Spelling In Typical Educational Enviromentioning
confidence: 99%